ASSESSMENT OF HETEROSIS AND INBREEDING DEPRESSION IN COTTON (GOSSYPIUM HIRSUTUM L.) - PATEL KOMAL; MADARIYA R. B; RAIYANI G. D.; LATA RAVAL (The Bioscan, 2014)
Six generation of four crosses viz., G.Cot 12 × MR 786, G.Cot 16 × GIHV 95 – 145, G.Cot 20 × GJHV 503 and 76 IH 20 × GBHV 148 derived from eight genotypes were evaluated to study heterosis and inbreeding depression for seed cotton yield and its component traits. For seed cotton yield and its component traits crosses viz., G.Cot 20 × GJHV 503 and 76 IH 20 × GBHV 148 showed significant positive heterosis over better parent along with significant positive inbreeding depression. The crosses, G.Cot 20 × GJHV 503 and 76 IH 20 × GBHV 148 also recorded significant positive heterobeltiosis for number of bolls per plant as well as boll weight with significant positive inbreeding depression. The present study reveals good scope for isolation of pure lines from the progenies of heterotic F2 s and significant positive inbreeding depression as well as commercial exploitation of heterosis in cotton.